2002
DOI: 10.1145/571697.571701
|View full text |Cite
|
Sign up to set email alerts
|

The performance of circuit switching in the internet

Abstract: --This paper studies the performance of anInternet that uses circuit switching instead of, or in addition to, packet switching. On the face of it, this would seem a pointless exercise; the Internet is packet switched, and was deliberately built that way to enable the efficiencies afforded by statistical multiplexing, and the robustness of fast re-routing around failures. But link utilization is low, and falling, particularly at the core of the Internet, which means that statistical multiplexing is less importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…No buffering is required in the communication path. Recently, there has been a renewed interest for CS in the communication systems and Internet [5,6]. The main reason is that it is now possible to build extremely high capacity all-optical switches using this technology, whereas it is not possible to design them using Packet Switching.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…No buffering is required in the communication path. Recently, there has been a renewed interest for CS in the communication systems and Internet [5,6]. The main reason is that it is now possible to build extremely high capacity all-optical switches using this technology, whereas it is not possible to design them using Packet Switching.…”
Section: Introductionmentioning
confidence: 99%
“…Circuit switches are characterized by simple data paths requiring no per-packet processing, and no packet buffers. In the literature [5], it is shown that a core of the network, where access links limit the maximum flow rate, and where high capacity is mostly needed, employing CS, warrants higher performance. In addition, there are no storage requirements at the routers, since no data is sent until the circuit has been established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent of any implementation success of FTM, it can be expected that many aspects of this universal switching technique will be improved, analyzed, and compared in the coming years. Return to circuit-switching for optical Internet is also addressed in (Molinero-Fernandez, McKeown, 2003).…”
Section: Introduction Scenario and Future Researchmentioning
confidence: 99%
“…Recently there has been renewed interest in CS because of the ease of building very high capacity circuit switches. In [5] it is shown that the core of the network, where access links limit the maximum flow rate, and where high capacity is needed most, there is a little or no difference in performance between CS and PS or WS. Given that CS can be built to have higher capacity than other well-known switching methods, this suggests that CS warrants further investigations.…”
Section: Introductionmentioning
confidence: 99%